Compensation Consultants and the Level, Composition, and Complexity of CEO Pay - Murphy, Kevin J.; Sandino, Tatiana (The Accounting Review, 2020)
ABSTRACT We provide fresh evidence regarding the relation between compensation consultants and CEO pay. First, firms that employ consultants have higher-paid CEOs—this result is robust to firm fixed effects and matching on economic and governance variables. Second, while this relation is partly due to consultant conflicts of interest, it is largely explained by the impact consultants have on the composition and complexity of CEO pay plans; notably, this impact fully mediates the consultant-CEO pay relation. Third, firms with higher-paid CEOs and more complex pay plans are more likely to hire a consultant. Last, Say-on-Pay voting patterns suggest shareholders view positively the advice consultants provide, but only when consultants provide no other services. We also find suggestive evidence of boards “layering” new equity incentive plans over existing ones, thereby increasing the impact of composition and complexity on CEO pay beyond the premium the CEO would demand for bearing additional compensation risk. JEL Classifications: J33; M12; M52; M48. Data Availability: Data are available from the public sources cited in the text.